Business Communication Five Core Competencies - Lucas, Kristen; Rawlins, Jacob D.; Haugen, Jenna (Open textbook library., 2023)
Business Communication: Five Core Competencies is a practical, engaging book designed to help undergraduate students and business professionals develop competence and build confidence in their business writing skills. Readers will learn about the five core competencies of business communication: professional, clear, concise, evidence-driven, and persuasive. They also will learn strategies for applying each of these competencies across a range of real-world business scenarios. Each chapter includes Communication Tips, Your Turn Exercises, and how-to advice for writing a variety of business messages.